Comparative study of enzyme-catalyzed biodegradation and crystallization behavior of PCL-PTEGMA amphiphilic hypergraft copolymers. (15th July 2020) - Zaheer, Muhammad; Yang, Jinxian; Wang, Xu; Li, Lianwei
Graphical abstract: Synthesis of self assembled hypergraft from HB-PCLn - g -PTEGMAm and enzyme-catalyzed biodegradation mechanism. Highlights: Hypergrafts were prepared with varied degree of polymerization of PCL and PTEGMA. Degree of branching and effect of subchain length were studied for HB-PCLn - g -PTEGMAm . Biodegradation time of hypergrafts was fine-tuned from few days to few hours. Crystallinity of PCL was controlled from ~0 (lowest limit) to ~52% (highest limit). Abstract: This work aims to systematically elucidate the biodegradation and crystallization behaviors of the model hypergraft systems made of poly( ε -caprolactone) (PCL) and poly[tri(ethylene glycol) methyl ether acrylate] (PTEGMA) blocks. A series of hyperbranched PCL (HB-PCLn ) with varied subchain lengths were synthesized using AB2 -type macromonomers with different degrees of polymerization ( DP s). The HB-PCLs were grafted with linear PTEGMA chains to prepare amphiphilic hypergraft copolymers (HB-PCLn - g -PTEGMAm ) to eventually get self-assembled structures through micellization. The DP of PTEGMA was also varied to get two sets of samples with varied sub-chain lengths of the hyperbranched core and the linear corona within each individual set to systematically study the crystallization and biodegradation behaviors of PCL. Differential scanning calorimetric (DSC) measurements of both hypergrafts and linear precursors were compared in order to get insights into the crystallization pattern of PCL. We found that the degree of crystallization in PCL can be controlled from ~0 (lowest limit) to ~52% (highest limit) by structural regulation. Biodegradation studies were performed in aqueous medium with Lipase from Pseudomonas using dynamic light scattering (DLS). A model was proposed to correlate the sub-chain length of core, the chain length of corona with the biodegradation rate of PCL, which reveals that an increase of PCL content in HB-PCLn - g -PTEGMAm increases the crystallinity while decreases the rate of biodegradation in a predictable manner.